2021
DOI: 10.3390/md19050261
|View full text |Cite
|
Sign up to set email alerts
|

Jorunnamycin A Suppresses Stem-Like Phenotypes and Sensitizes Cisplatin-Induced Apoptosis in Cancer Stem-Like Cell-Enriched Spheroids of Human Lung Cancer Cells

Abstract: It has been recognized that cancer stem-like cells (CSCs) in tumor tissue crucially contribute to therapeutic failure, resulting in a high mortality rate in lung cancer patients. Due to their stem-like features of self-renewal and tumor formation, CSCs can lead to drug resistance and tumor recurrence. Herein, the suppressive effect of jorunnamycin A, a bistetrahydroisoquinolinequinone isolated from Thai blue sponge Xestospongia sp., on cancer spheroid initiation and self-renewal in the CSCs of human lung cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 84 publications
0
16
0
Order By: Relevance
“…Jorunnamycin A was isolated from the Thai blue sponge, Xestospongia sp., which was collected by SCUBA diving in the vicinity of Si-Chang Island, Chonburi Province, Thailand [21]. Solvents, which included ethyl acetate, dichloromethane, and hexane, were distilled before use.…”
Section: Semisynthesis Of 22-(4 Py)-ja From Jorunnamycin Amentioning
confidence: 99%
See 1 more Smart Citation
“…Jorunnamycin A was isolated from the Thai blue sponge, Xestospongia sp., which was collected by SCUBA diving in the vicinity of Si-Chang Island, Chonburi Province, Thailand [21]. Solvents, which included ethyl acetate, dichloromethane, and hexane, were distilled before use.…”
Section: Semisynthesis Of 22-(4 Py)-ja From Jorunnamycin Amentioning
confidence: 99%
“…was able to induce apoptosis via p53 modulation, inhibit cancer metastasis, and suppress cancer stemness behaviors [17][18][19]. Recently, jorunnamycin A found in a similar blue sponge displayed intriguing antimetastatic activity and attenuated cancer stem-cell-like phenotypes [20,21], suggesting that jorunnamycin A is a potential lead compound for the development of novel anticancer agents with greater potency.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evidence has been reported that CSC is the main factor responsible for cancer aggression, maintenance, avoidance of the immune system, and metastasis [64,65]. Single cancer cell culture under detachment conditions with the nutrients and growth factors needed to form tumor spheroids, known as single 3D spheroid-formation assay, has been used to evaluate the CSC property [66,67]. Our results distinctly revealed that the enlargement of NCI-H23 tumor spheroids in a CSC-enriched population was diminished with caffeine treatment (Figure 4d,e).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to 2D tumor cell culture, tumor spheroids are unique in recapitulating tissue architectures, mimicking the nutrition, metabolic, and proliferative gradients of in vivo tumors, and demonstrating clinically relevant chemoresistance [ 8 , 9 , 10 , 11 ]. More importantly, studies have revealed that tumor spheroids served as surrogate systems to evaluate cancer stem cell (CSC)-related characteristics in vitro [ 12 , 13 ]. Yamazaki et al cultured liver cancer and breast cancer cell lines on a polymer thin film to promote tumor spheroid formation.…”
Section: Introductionmentioning
confidence: 99%